A New Comparison Theorem and Stability Analysis of Fractional Order Cohen-Grossberg Neural Networks - Liu, Xiaolei; Yuan, Jian; Zhou, Gang; Zhao, Wenfei (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper proposes a new comparison theorem and stability analysis of fractional order Cohen-Grossberg neural networks. Firstly, a new comparison theorem for fractional order systems is proved. Secondly, the stability of a class of fractional order Cohen-Grossberg neural networks with Caputo derivative is investigated on the basis of the above comparison theorem. Thirdly, sufficient conditions of stability of the neural networks are obtained utilizing the property of Mittag-Leffler functions, the generalized Gronwall-Bellman inequality and the method of the integral transform. Furthermore, a numerical simulation example is presented to illustrate the effectiveness of these results.